Study of Growing Grapes Technique for Malware Detection (International Journal of Engineering and Computer Science, 2015)
The Behavior based detection is promising to solve the pressing security problem of malware. The great challenge lies in how to detect malware in a both accurate and light-weight manner. The Behavior based detection method, named growing grapes, aiming to enable accurate online detection. It consists of a clustering engine and detection engine. The clustering engine groups the objects, e.g., processes and files, of a suspicious program together into a cluster, just like growing grapes. The detection engine recognizes the cluster as malicious if the behaviors of the cluster match a predefined behavior template formed by a set of discrete behaviors. Malware based on multiple behaviors and the source of the processes requesting the behaviors. Light-weight as it uses OS level information flows instead of data flows that generally impose significant performance impact on the system. To further improve the performance, a novel method of organizing the behavior template and template database is proposed, which not only makes the template matching process very quick, but also makes the storage space small and fixed. Furthermore, the detection accuracy and performance are optimized to the best degree using a combinatorial optimization algorithm, which properly selects and combines multiple behaviors to form a template for malware detection. Finally, malicious OS objects in a cluster fashion rather than one by one as done in traditional methods, which help users to thoroughly eliminate the changes of a malware without malware family knowledge.